Relationship between major depressive disorder and myalgic encephalomyelitis/chronic fatigue syndrome: a two-sample mendelian randomization study analysis - Wenjing Song; Xinlei Hou; Minmin Wu; Luwen Zhu (Scientific Reports)
Abstract Major depressive disorder (MDD) and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) frequently occur together; yet their causal relationship remains unclear. To investigate the potential genetic causal link between these conditions, we conducted a two-sample Mendelian randomization (MR) analysis. Summary data from Genome-Wide Association Studies (GWAS) for MDD were sourced from the UK Biobank and the Psychiatric Genomics Consortium, while GWAS data for ME/CFS were retrieved from the UK Biobank. Inverse-variance weighting (IVW), the MR-Egger method, and weighted median, simple and weighted modes were used to perform the MR analysis. In addition, Cochrane’s Q-test was used to detect heterogeneity among the MR results. Horizontal pleiotropy was detected using the MR-Egger intercept and the MR pleiotropy residual sum and outlier (MR-PRESSO) tests. Leave-one-out analysis was performed to investigate the sensitivity of the association between MDD and ME/CFS. The results of the MR analysis revealed no causal relationship between MDD and ME/CFS. The pleiotropy test revealed that causality bias was improbable, and no evidence of heterogeneity was found among the genetic variants. Finally, the leave-one-out test confirmed the stability and robustness of our findings.